2006
DOI: 10.1152/ajpheart.01070.2005
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen modulates the mechanical homeostasis of mouse arterial vessels through nitric oxide

Abstract: . Estrogen modulates the mechanical homeostasis of mouse arterial vessels through nitric oxide. Am J Physiol Heart Circ Physiol 290: H1788 -H1797, 2006. First published November 23, 2005 doi:10.1152/ajpheart.01070.2005We have recently shown that estrogen causes vessel dilation through receptor-mediated stimulation of nitric oxide (NO) production. Here, we hypothesize that estrogen modulates the mechanical homeostasis in the blood vessel wall through NO production. The mechanical properties of female ovariecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
3
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 39 publications
3
23
3
4
Order By: Relevance
“…This finding is consistent with a previous study that showed that systemic arteries from OVX female mice were less compliant than those of intact female mice (8). We confirmed the impact of this compliance decrease in vivo by measuring pulmonary pressures in a subgroup of OVX mice treated with estrogen or placebo after 21 days of SuHx.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with a previous study that showed that systemic arteries from OVX female mice were less compliant than those of intact female mice (8). We confirmed the impact of this compliance decrease in vivo by measuring pulmonary pressures in a subgroup of OVX mice treated with estrogen or placebo after 21 days of SuHx.…”
Section: Discussionsupporting
confidence: 92%
“…[ 47 ] Chondrocytes have been successfully cultured on alginate gels that are mechanically similar to cartilage with a Young's modulus at or greater than 75 kPa. [ 48 ] The Young's modulus of the photoelastomer evaluated in the present study could be modifi ed by altering the chemical composition; using the present formulation, the Young's modulus of 96 kPa was similar to that of skeletal muscle, [ 38 ] the spinal cord, [ 39 ] arteries, [ 40 ] and other tissues. [ 49 ] While the effects of stiffness are not necessarily required in static monolayer cell culture, a customized stiffness value is suitable for other biological applications such as use in mechanically dynamic culture or in implants; materials in these applications are subjected to repeated or cyclical mechanical stress.…”
Section: Discussionmentioning
confidence: 78%
“…The photoelastomer formulation described above with a value of 96 kPa was selected for further study due to the biomedical applicability of this material for regeneration of skeletal muscle, arteries, and other tissues. [38][39][40] …”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…The data suggest that the strain and stress of the vessel showed a significant linear relation while the modulus of the vessel revealed an inverse relation with NO production. 11 Those data reflect a relationship between the endothelial function and the mechanical property of the femoral and carotid arteries of the adult male, female, ovariectomized and eNOS -/-female mice. Similar findings were made in coronary arteries of control mice and those exposed to cigarette smoke.…”
Section: Mechanical Properties and Endothelial Functionmentioning
confidence: 93%
“…Recently, Guo et al have shown significant correlation between nitrite and vessel wall thickness, strain, stress and elastic modulus under the influence of estrogen 11 in femoral arteries and cigarette smoke in coronary artery 12 of mice. In a postnatal model, Huang et al 14 investigated the axial variations of geometry (diameter and length), and mechanical properties (stress-stain relation, elastic modulus and compliance) of the C57BL mice aorta from the aortic valve to the common iliac.…”
Section: Introductionmentioning
confidence: 99%